UTILIZATION OF TECHNOLOGY IN THE PROCESS OF DISPUTE RESOLUTION IN RELIGIOUS COURTS - Hidayat, Asep Syarifuddin (JURNAL ILMU SYARIAH, 2023)
Resolving disputes is a crucial aspect of the justice system that requires efficacy, accessibility, and superiority. In an increasingly technologically advanced era, religious courts must also embrace technology as an effective dispute-resolution tool. This article discusses the urgency and significance of employing technology in religious court dispute resolution. Numerous significant advantages can be derived from using technology in religious courts. For instance, technology can improve productivity by streamlining administrative and case management procedures. Electronic delivery of trial notices and related informationmakes it simpler for interested parties to access the latest news and follow the legal process. Technology can also enhance society's accessibility. Additionally, applying technology in religious tribunals can improve the quality of dispute resolution. The method used in this research is a qualitative research method with a literature and statutory approach. The results of the study state that some challenges and obstacles need to be overcome in the application of technology in dispute resolution in Religious Courts. Attention must be paid to the limitations of technological infrastructure, data security, and privacy, as well as adoption andadaptation by related parties. Therefore, it is recommended that associated parties provide judges and court personnel with adequate technical training and education and devise regulations that support the Use of technology in dispute resolution.